Air quality in the operating room: Surgical site infections, HVAC systems and discipline - position paper of the German Society of Hospital Hygiene (DGKH) - Popp, Walter; Alefelder, Christof; Bauer, Sonja; Daeschlein, Georg; Geistberger, Petra; Gleich, Sabine; Herr, Caroline; Hübner, Nils-Olaf; Jatzwauk, Lutz; Kohnen, Wolfgang; Külpmann, Rüdiger; Lemm, Friederike; et al. (German Medical Science GMS Publishing House, 2019)
In recent years, there has been an ongoing discussion about the value of laminar airflow (LAF=low turbulence displacement ventilation) in the operating room for prevention of surgical site infections (SSI). Some publications, e.g., from the WHO, issued the demand to no longer build LAF ceilings in operating rooms. The present statement deals critically with this position and justifies the use of LAF ceilings in different ways:Thus, this paper recommends building LAF ceilings in the future as well, depending on the operations intended.Further, this paper gives an overview of possible reasons for surgical site infections and highlights the importance of discipline in the operating theatre.